POTENSI AIR REBUSAN KEDELAI SEBAGAI MEDIA ALTERNATIF PERBANYAKAN BAKTERI Pseudomonas fluorescens SEBAGAI AGEN HAYATI - Alfi Nurwahidah; Trisnani Alif (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Pseudomonas fluorescens is a bacterial antagonist that is widely used as a biological control agent. Propagation of Pseudomonas fluorescens is mostly done with synthetic agar media. This requires an expensive cost, therefore there is a need for alternative media for bacterial propagation. This study aims to examine the growth of Pseudomonas fluorescens in liquid media of soybean cooking water. The research was carried out at the Office of the TPH Protection Coordinator for the Bojonegoro Region. The research method used is descriptive quantitative method. carried out on the number of bacterial colonies. The results of this study indicate that soybean cooking water can be used as a medium for propagation of Pseudomonas fluorescens bacteria and has a high bacterial density with the number of bacterial colonies of 6.5×108 CFU/ml in the first week.